The Potential of Probiotics for Modulating The Gut-Brain Axis to Enhance Cognitive Function: A Narrative Review - Latuconsina, Farhan Aimarsa; Kasasiah, Ahsanal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Cognitive decline is an important health issue because it is closely linked to chronic inflammation, oxidative stress, impaired intestinal barrier function, and microbial imbalance, all of which accelerate neuronal aging and increase the risk of neurodegenerative diseases. This article aims to review and analyze the biological mechanisms through which probiotics modulate communication between the digestive tract and the brain and how these mechanisms relate to cognitive outcomes. This review discusses key mechanistic pathways reported in the literature, including enhanced production of neurotransmitters such as gamma aminobutyric acid, serotonin, and dopamine; increased short chain fatty acids; improved integrity of the intestinal barrier and the blood–brain barrier; reduced inflammatory activity; increased neurotrophic factors; and regulation of physiological stress responses. Synthesis of the seven included studies shows that probiotics improve cognition through interconnected pathways that support memory performance, synaptic plasticity, and mood stability, and may prevent cognitive impairment associated with aging, inflammation, or postoperative stress. The implications of these findings suggest that probiotics hold considerable potential as a supportive approach for brain health, although their effectiveness depends on strain selection, dose, and duration. This article provides a comprehensive overview of mechanistic consistency across studies and offers a foundation for future research aimed at identifying optimal probiotic strategies to enhance cognitive function.